Biomechanical Assessment of a Distally Fixed Lateral Extra-articular Augmentation Procedure in the Treatment of Anterolateral Rotational Laxity of the Knee. Issue 9 (July 2019) - Devitt, Brian M.; Lord, Breck R.; Williams, Andy; Amis, Andrew A.; Feller, Julian A.
Background: Most lateral extra-articular tenodesis (LET) procedures rely on passing a strip of the iliotibial band (ITB) under the fibular (lateral) collateral ligament and fixing it proximally to the femur. The Ellison procedure is a distally fixed lateral extra-articular augmentation procedure with no proximal fixation of the ITB. It has the potential advantages of maintaining a dynamic element of control of knee rotation and avoiding the possibility of overconstraint. Hypothesis: The modified Ellison procedure would restore native knee kinematics after sectioning of the anterolateral capsule, and closure of the ITB defect would decrease rotational laxity of the knee. Study Design: Controlled laboratory study. Methods: Twelve fresh-frozen cadaveric knees were tested in a 6 degrees of freedom robotic system through 0° to 90° of knee flexion to assess anteroposterior, internal rotation (IR), and external rotation laxities. A simulated pivot shift (SPS) was performed at 0°, 15°, 30°, and 45° of flexion. Kinematic testing was performed in the intact knee and anterolateral capsule–injured knee and after the modified Ellison procedure, with and without closure of the ITB defect. A novel pulley system was used to load the ITB at 30 N for all testing states. Statistical analysis used repeated measures analyses of variance and paired t tests with Bonferroni adjustments. Results: Sectioning of the anterolateral capsule increased anterior drawer and IR during isolated displacement and with the SPS (mean increase, 2° of IR; P < .05). The modified Ellison procedure reduced both isolated and coupled IR as compared with the sectioned state ( P < .05). During isolated testing, IR was reduced close to that of the intact state with the modified Ellison procedure, except at 30° of knee flexion, when it was slightly overconstrained. During the SPS, IR with the closed modified Ellison was less than that in the intact state at 15° and 30° of flexion. No significant differences in knee kinematics were seen between the ITB defect open and closed. Conclusion: A distally fixed lateral augmentation procedure can closely restore knee laxities to native values in an anterolateral capsule–sectioned knee. Although the modified Ellison did result in overconstraint to isolated IR and coupled IR during SPS, this occurred only in the early range of knee flexion. Closure of the ITB defect had no effect on knee kinematics. Clinical Relevance: A distally fixed lateral extra-articular augmentation procedure provides an alternative to a proximally fixed LET and can reduce anterolateral laxity in the anterolateral capsule–injured knee and restore kinematics close to the intact state.